Acquired Visual Deficits Independent of Lesion Site in Acute Stroke - Wijesundera, Chamini; Vingrys, Algis J.; Wijeratne, Tissa; Crewther, Sheila G. (Frontiers in Neurology, 2020)
Most clinical diagnoses of stroke are based on the persistence of symptoms relating to consciousness, language, visual-field loss, extraocular movement, neglect (visual), motor strength, and sensory loss following acute cerebral infarction. Yet despite the fact that most motor actions and cognition are driven by vision, functional vision per se is seldom tested rigorously during hospitalization. Hence we set out to determine the effects of acute stroke on functional vision, using an iPad application (Melbourne Rapid Field-Neural) that can be used to assess vision (visual acuity and visual field sensitivity) at the bedside or in the emergency ward in about 6 min per eye. Our convenience sample comprised 60 (29–88 years, 65 ± 14 years, 33 males) of 160 sequentially presenting first episode, acute (<7 days) ischemic stroke patients at Sunshine Hospital, Melbourne. One hundred patients were excluded due to existing eye disease, inadequate radiological confirmation, inability to comply with English directions or too ill to participate. Stroke cases were compared with 37 (29–85 years, 64 ± 12 years,14 males) similar-aged controls using a Mann-Whitney U-test. A significant loss in visual field sensitivity was measured in 68% of stroke cases (41/60, Mean Deviation: Stroke: −5.39 ± 6.26 dB, Control: 0.30 ± 0.60 dB, MWU = 246, p < 0.0001). Surprisingly, 44% (18/41) of these patients were unaware of their field loss. Although high contrast visual acuity was unaffected in most (55/60) patients, visual acuity-in-noise was reduced in 62% (37/60, Stroke: mean 6/12−2, log MAR 0.34 ± 0.21 vs. Control: mean 6/7·5–2, log MAR 0.14 ± 0.10; MWU = 470, p < 0.0001). Visual field defects were associated with all occipital, parietal and posterior cerebellar artery strokes while 9/15 middle cerebral artery lesions and 11 lesions in other brain regions were also associated with visual field defects. Our findings demonstrate that 2/3 of acute first episode ischemic stroke patients experience acquired vision deficits, often unrelated to the confirmed lesion site. Our results also imply that visual dysfunction may be associated with a more generalized cerebral dysfunction while highlighting the need for bedside testing of vision for every stroke patient and demonstrating the translational clinical value of the “Melbourne Rapid Field- Neural” iPad application. Clinical Trial:http://www.ANZCTR.org.au/ACTRN12618001111268.aspx.